How Can Intelligent Persona Systems Support Online Advertisers’ Daily Work Tasks? - Salminen, Joni; Kaate, Ilkka; Olkkonen, Rami; Yang, Yanwu; Jung, Soon-Gyo; Jansen, Bernard J. (Springer, 2026)
This chapter discusses the role of personas—more particularly, intelligent personas—which are personas enabled by intelligent systems, in online advertising work. Through a conceptual analysis, we find that intelligent personas can contribute to all central parts of the online advertising work process, including segmentation, targeting, ad creation, account structuring, optimization, and reporting. We discuss an intelligent advertising system in which personas are a central hub for actions.
The Design of Human-Centered Artificial Intelligence for the Workplace